Developmental protein kinase C hyper-activation results in microcephaly and behavioral abnormalities in zebrafish. Issue 1 (December 2018) - Liu, Taian; Shi, Yujian; Chan, Matthew; Peng, Gang; Zhang, Quan; Sun, Xiao; Zhu, Zeyao; Xie, Yuxin; Sham, Kathy; Li, Jianzhen; Liu, Xiaodong; Ho, Idy; et al.
Abstract Susceptible genetic polymorphisms and altered expression levels of protein kinase C (PKC)-encoding genes suggest overactivation of PKC in autism spectrum disorder (ASD) development. To delineate the pathological role of PKC, we pharmacologically stimulated its activity during the early development of zebrafish. Results demonstrated that PKC hyper-activation perturbs zebrafish development and induces a long-lasting head size deficit. The anatomical and cellular analysis revealed reduced neural precursor proliferation and newborn neuron formation. β-Catenin that is essential for brain growth is dramatically degraded. Stabilization of β-catenin by gsk3β inhibition partially restores the head size deficit. In addition, the neuropathogenic effect of developmental PKC hyper-activation was further supported by the alterations in the behavioral domain including motor abnormalities, heightened stress reactivity and impaired habituation learning. Taken together, by causally connecting early-life PKC hyper-activation to these neuropathological traits and the impaired neurogenesis, these results suggest that PKC could be a critical pathway in ASD pathogenesis.